2005
DOI: 10.1163/22941932-02603006
|View full text |Cite
|
Sign up to set email alerts
|

Radial Variations of Anatomical Characteristics and Specific Gravity in Eucalyptus Camaldulensis Clones

Abstract: Five superior clones of Eucalyptus camaldulensis from in vitro propagation or tissue culture at the Sra Keaw plantation site in the eastern part of Thailand were selected for examining radial variations of anatomical characteristics and specific gravity. The age of the clones was 5 years at harvest. A 9-year-old tree grown from seed in the same site was also investigated. Results were as follows: 1) Mean specific gravity showed significantly different values among the 5 clones and the seedling. 2) Vessel densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…Basic density in the outer wood (2 cm from the bark side) collected from 15 half-sib families of 5-year-old E. camaldulensis ranged from 0.51 to 0.61 g cm −3 (Kuramochi et al 2014). Overall, our values obtained in basic density were lower than those obtained by previous researches (Veenin et al 2005;Kuramochi et al 2014). There were significant among-family differences in green moisture content at 5.2 m height and basic density at 1.2 and 5.2 m heights (Table 2).…”
Section: Green Moisture Content and Basic Densitycontrasting
confidence: 94%
See 1 more Smart Citation
“…Basic density in the outer wood (2 cm from the bark side) collected from 15 half-sib families of 5-year-old E. camaldulensis ranged from 0.51 to 0.61 g cm −3 (Kuramochi et al 2014). Overall, our values obtained in basic density were lower than those obtained by previous researches (Veenin et al 2005;Kuramochi et al 2014). There were significant among-family differences in green moisture content at 5.2 m height and basic density at 1.2 and 5.2 m heights (Table 2).…”
Section: Green Moisture Content and Basic Densitycontrasting
confidence: 94%
“…The mean value of all of the trees at 1.2 m height (0.50 g cm −3 ) was lower than that at 5.2 m height (0.53 g cm −3 ). Veenin, Fujita, Nobuchi and Siripatanadilok (2005) reported that the mean values of basic density in 5-year-old E. camaldulensis clones planted in Thailand ranged from 0.61 to 0.73 g cm −3 . Moreover, Malan (1993) also reported that wood density varied from about 0.60 to 0.87 g cm −3 in 12-year-old eucalypt hybrids trees, reaching an average density of up to 0.96 g cm −3 when they became fully mature.…”
Section: Green Moisture Content and Basic Densitymentioning
confidence: 99%
“…Although the positions (at a distance from the pith) at which the peak values occurred were not the same among growth categories, radial profiles were almost similar among growth categories. It has been reported that BD increases from pith to bark in E. camaldulensis (Veenin et al 2005), E. saligna (Ohbayashi and Shiokura 1990;DeBell et al 2001), E. nitens (Evans et al 2000), E. albnes, E. bancroftii, E. dealbata, E. goniocalyx, E. macrothyncha, and E. sideroxylon (Wilkes 1984). In contrast, in E. tereticornis, Sharma et al (2005) reported that specific gravity was almost constant from pith to a certain position and then gradually decreased towards the bark.…”
Section: Resultsmentioning
confidence: 94%
“…It has been reported that BD increases from pith to bark in E. camaldulensis (Veenin et al . 2005), E. saligna (Ohbayashi and Shiokura 1990; DeBell et al . 2001), E. nitens (Evans et al .…”
Section: Resultsmentioning
confidence: 99%